Alternative payment models and innovation: a case study of US health system adoption of a sacubitril/valsartan to treat acute decompensated heart failure. (1st December 2020) - Shafrin, Jason; Aliyev, Elmar R.; Brauer, Michelle; Park, Siyeon; Shen, Xian
Abstract: Aim: To understand the financial impact of health system adoption of novel heart failure medications under US alternative payment models (APMs). Materials and methods: This study used a decision tree model to assess the financial impact of health system adoption of sacubitril/valsartan to treat acute decompensated heart failure (ADHF). A comparator scenario modeled current health care utilization and cost for treating hospitalized ADHF patients with angiotensin-converting-enzyme inhibitors (ACEi) or angiotensin-receptor blockers (ARB). The study then measured the impact of adopting sacubitril/valsartan to treat ADHF on health system economic outcomes. Differences in treatment efficacy were based on the PIONEER-HF clinical trial. The financial impact of changes in patient outcomes under the sacubitril/valsartan and ACEi/ARB arms was assessed across three APMs: the Medicare Shared Savings Program, Bundled Payments for Care Improvement, and fee-for-service payments adjusted according to the Hospital Readmission Reduction Program. Results: Sacubitril/valsartan reduced re-hospitalizations after an initial ADHF admission by 46.3% for individuals aged 18– 64 years and 23.4% for individuals aged ≥65 years. Health systems' financial benefit of adopting sacubitril/valsartan was 740 per ADHF case per year (PCPY). Savings were larger for patients aged ≥65 years (803 PCPY) compared to those <65 years (653 PCPY). The majority of the health system financial benefit came from changes in APM bonus and penalty reimbursements. Value-based payments from the Hospital Readmission Reduction Program (1, 190 financial gain PCPY) and the Bundled Care Payment Improvement Initiative (645 financial gain PCPY) produced larger financial benefits than participation in the Medicare Shared Savings Program (253 financial gain PCPY). Limitations: The model uses clinical trial data, which may not reflect real-world outcomes. Further, the financial implications were modeled based only on three widely used APMs. Conclusion: Sacubitril/valsartan adoption decreased hospitalizations and led to a positive net financial impact on health systems after accounting for APM bonus payments.